Internal migration in Malaysia : evidence from censuses. - Hassan, Abdul Rahman
This paper is concerned with recent changes in levels and patterns of migration in Malaysia. It shows that the incidence of internal migration has increased. In 1970 the migration ratio was 347 per 1,000 population but this increased to 376 per 1,000 in 1980. However,the net migrating states,i.e. the Federal Territory,Selangor and Pahang remain unchanged since the 1970 census. The sectoral movements show the importance of the intrasectoral movement with 45 per cent of the migrants involved in the rural to rural movement. Social reasons including marriage and to follow family were the most important reasons given by internal migrants on Malaysia for moving.